Digital Agriculture: A Literature Review of Social, Economic and Education Trends - Ahlam A. skib; Laila S. Mousay (African Journal of Advanced Pure and Applied Sciences, 2023)
Agriculture is the main source of food in the world. Stable agricultural sector ensures food security for countries, and it is the most important domain in the economic and social development of any country. With the increase in population density, the need for food increases, which leads countries to find quick solutions to meet the food needs of their population and provide security. And the world today is facing the challenge of global greenhouse gas pollution, Therefore, digital agriculture is considered necessary and inevitable in the near future, especially with the tremendous technological development in various technical and economic fields, knowing that traditional agriculture is financially costly due to the absence of modern technologies that provide accurate information and digital statistics that markets and production process need, while Relying on digital farming techniques will inevitably contribute to the development of local production at a lower cost, which will contribute to the high competitiveness of local agricultural production and thus achieve structural and sustainable economic growth, and farmers urgently need to prepare to embrace the coming digital change and must increase or acquire new skills and capabilities in the field of information and communication technology. This paper points out the gap on how to build the current body of knowledge about digital agriculture. With the aim of bridging this gap, our paper presents a review of the digital agriculture literature that helps realize the importance of enhancing research capacity and socioeconomic transformation by enhancing the connection with agricultural research knowledge in the field of agricultural informatics and the impact of these technological innovations on society.